Economic Security in Border Areas: The Fulfillment of Community Welfare - Budi Hermawan Bangun; Fatma Muthia Kinanti; Muhammad Rafi Darajati (Lampung Journal of International Law)
Border area management entails navigating geographical complexity and socio-cultural diversity, necessitating a comprehensive approach that integrates security and welfare. This article highlights a paradigm shift from traditional to economic security, recognizing economic dependence as a potential national vulnerability. Despite challenges like geographic remoteness and economic inequality, border regions are vital for economic growth. Using a conceptual approach, the article emphasizes the need to balance security and welfare through cross-border trade development and community empowerment. While Law Number 43 of 2008 aims to manage borders, unclear authority and regulatory overlap hinder effectiveness, compounded by military-focused defense strategies, limited budgets, and inadequate infrastructure. To address these issues, enhancing international cooperation, clarifying authority, and empowering communities through local wisdom are essential. Such empowerment is expected to bolster self-esteem, reduce economic dependency, and strengthen economic security, emphasizing the importance of balancing protection with economic development. Strategies like expanding trade zones and enhancing social capital, alongside infrastructure development and improved social services, are crucial for ensuring access and fostering the welfare of border communities.